Pillararene-based donor–acceptor complex for ferroelectric self-assembled supramolecular materials - Shuai Cao; Leqian Song; Yangyang Zheng; Kim Truc Nguyen; Huacheng Zhang; Jie Han (APL Materials, 2024)
The investigation of ferroelectric materials is an important aspect of condensed matter physics. Compared to the traditional inorganic ferroelectric ones, organic ferroelectric materials possess unique advantages, including light weight, scalability, flexibility, and solvent treatability. However, the study of organic ferroelectric materials is still in its infancy, especially from the view of supramolecular chemistry; various mechanisms of forming self-assembly and thus diverse building blocks employed are not yet to be further developed. Herein, a pillararene-based charge transfer (CT) self-assembly was produced by utilizing pillar[5]quinone (P5Q) as the electron acceptor and phenothiazine (PTZ) as the electron donor. Compared to the intrinsic P5Q, our fabricated donor–acceptor complex displays particular intriguing features, such as the enhanced second-harmonic generation and ferroelectric responses, benefiting from the CT interaction between P5Q and PTZ. The current work provides a unique strategy for the successful construction of supramolecular ferroelectrics.